FOREIGN EXPERIENCE OF KNOWLEDGE EXCHANGE BETWEEN EDUCATORS AT HIGHER EDUCATION INSTITUTIONS (Innovative professional education, 2024)
The theses showed a cross-cultural study of knowledge exchange between educators. Articles were taken between the two continents (North America and Asia). The theses compare scientists between their researches conducted in countries (USA and Malaysia), analyze the reasons why the exchange of knowledge between educators in higher education institutions is not sufficiently investigated and indicate the main factors why educators are reluctant to exchange knowledge.
Keywords: professional competence, knowledge exchange, research results, educators